Influence of Flood Pulse on Termite Diversity (INSECTA: ISOPTERA) in the Pantanal - Tarik Godoy D. Plaza; Carla Galbiati (Sociobiology, 2017)
This research aimed to associate termite diversity to flood pulse by Paraguay River, and with savannas and pasture areas. The study was conducted nearby the town of Cáceres, in Pantanal - Mato Grosso, on six livestock farms subject to Paraguay River flood pulse. Types of land use sampled were native savanna and cultivated pasture. Flooded and dry plots were selected, both the savanna and the pasture in each sampling area. Termite richness and abundance was analysed based on the  environments as an explanatory variable (FP – flooded pasture, DP – dry pasture, FS – flooded savanna, DS – dry savanna) through GLM; Tukey’s test was subsequently performed to determine whether land use and/or flood pulse can significantly affect the termite community. There were 37 termite species and 19 genera. Richness and abundance of termite species cannot be explain by flooding pulse, but were explained only by land use (pasture and savanna). The similarity analysis also identified that species composition was quite affected by flood in grazing areas, but this disturbance does not affect the savanna areas. In conclusion, flood pulse is not a determining factor for savannas or pasture termite richness, but change the composition of the termite fauna in the environment.